Strategic Partnerships and Resource Mobilisations' of Community-Based Organisations in Kajiado County, Kenya - Mopel, Nailantei; Norvy, Paul; Wambugu , James (Journal of Business and Strategic Management, 2023)
Purpose: The research study aimed to investigate the influence of strategic partnerships on resource mobilisation of community-based organisations' in Kajiado County, Kenya. The specific objectives of the study include the role of joint activities, shared resources, and information sharing reciprocity on resource mobilisation among selected Community Based Organisations in Kajiado County, Kenya. The study was anchored on the Theory of Change and Resource Mobilisation Theory. Methodology: The study adopted an embedded mixed research design with quantitative and qualitative methods. The study's target population was 395 CBOs members in Kajiado County. The research used a simple random sampling technique with 30% to 10 simple CBOs. Purposive sampling was used to sample 10 managers, and Yamane's scientific formula (1967) to sample 395 staff. A sample size of 310 was used in the study. Data collection was done using questionnaires, which were administered online. Descriptive statistics, including frequency tables, graphs, and charts, were used, including questionnaires and interview guides. Quantitative data was collated and analysed using descriptive statistics such as measures of central tendency and dispersion through the use of SPSS (Version 25). The analysed data was presented in the form of figures, tabulations, graphs, and charts. Qualitative data was analysed thematically with explanations according to each objective and presented in narrative form. Pearson correlation analysis was conducted to establish the relationship between the study variables. A multiple regression model was run to test the influence of predictor variables on the predicted variable. Findings: The regression coefficient results showed that all the independent variables (joint activities, shared resources, information sharing, and reciprocity) are statistically significant in predicting the dependent variable (resource mobilisation). The study concluded that it was evident that strategic partnerships had an influence on resource mobilisation. Unique Contribution to theory, practice and policy: The study recommended that community-based organisations engage with external stakeholders to promote effective program/project activities and implementation. This will positively affect the community economic development outcomes for the projects/programs. Also, training and capacity building on writing a winning proposal for the community groups to be conducted as it will be very relevant in resource mobilisation. Also, seek help from professionals and experts to increase their skills in writing proposals that impress donors. The study makes a significant contribution to theory and practice in strategic partnership and resource mobilisation.